Analisis Meningkatkan Simpan Pinjam Koperasi dan UKM (Usaha Kecil Menengah) pada Masa Covid-19 di Provinsi Sumatera Utara - Shyella Putri Mandasari; Muhammad Arif (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Cooperatives are a necessary and important economic institution. Cooperatives are a form of joint effort based on the principle of family to improve welfare. And cooperatives have a goal to increase economic activity. Cooperatives and MSMEs have contributed significantly to regional and national income, especially in the North Sumatra Province. MSMEs play a role in absorbing labor in the distribution of development results. During the COVID-19 pandemic, the majority of the economic sector, especially MSMEs, could not develop and many ended up in bankruptcy and a slowdown in the economic sector in Indonesia with its various derivatives. The Micro, Small and Medium Enterprises (MSMEs) sector which is the most important part of the economic sector that is feeling the impact of the COVID-19 pandemic. During the Covid-19 period, MSMEs experienced various problems such as decreased sales, capital, distribution was hampered, raw material difficulties, decreased production and the occurrence of many layoffs for workers and hunting which later became a threat to the national economy. With the purpose of this research, the analysis is to increase Savings and Loans for Cooperatives and Small and Medium Enterprises (UKM) during the Covid-19 period in North Sumatra Province, this research method is by taking secondary data and interviews, solving problems using qualitative methods from existing descriptions. in the mass media and then concluded by researchers. Keywords : Savings and Loans, UKM, Covid 19